2003
DOI: 10.1167/iovs.03-0219
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 5-Mediated Corneal Epithelial Inflammatory Responses toPseudomonas aeruginosaFlagellin

Abstract: Flagellin of Gram-negative pathogens such as PA contributes to the inflammatory responses of corneal epithelium in a TLR5-NF-kappaB signaling pathway-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
157
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(165 citation statements)
references
References 33 publications
7
157
0
1
Order By: Relevance
“…Activation of TLR2, TLR4, and TLR5 expressed by various epithelia can contribute to host defense by induction of cytokines (9,10,13,14,19,20) and antimicrobial peptides (3,12). In this study we examined the regulated expression and function of TLR5 and TLR9 on keratinocytes, given that our preliminary studies found that TLR5 and TLR9 were expressed in distinct microanatomic locations of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of TLR2, TLR4, and TLR5 expressed by various epithelia can contribute to host defense by induction of cytokines (9,10,13,14,19,20) and antimicrobial peptides (3,12). In this study we examined the regulated expression and function of TLR5 and TLR9 on keratinocytes, given that our preliminary studies found that TLR5 and TLR9 were expressed in distinct microanatomic locations of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, chemokines, and antimicrobial peptides produced by epithelial cells enable them to participate in innate and acquired immune responses (1)(2)(3)(4)(5)(6). In addition, epithelia express certain TLRs, which may contribute to their ability to sense and respond to invading pathogens (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal epithelial cells are located at the ocular surface, and in addition to providing a physical barrier function, they also mediate the immune response to microbial products through the production of proinflammatory cytokines, chemokines, and antimicrobial peptides (9,10). Furthermore, corneal epithelial cells express several TLRs and can respond in vitro to TLR2, TLR3, and TLR5 agonists (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Our previous studies demonstrated that TLR2, TLR4, and TLR9 are expressed in the cornea and can mediate corneal inflammation through the MyD88 adaptor molecule (19,22).…”
mentioning
confidence: 99%
“…Some studies have demonstrated the role of the flagellin of P. aeruginosa in induction of IL-6 and TNFα [24,28] or CXCL8 [37,38] during mouse infections. In this work, the inflammatory response following human keratinocyte and RHE infection with flagellin-deficient strains was strongly decreased.…”
Section: Discussionmentioning
confidence: 99%